Preoperative Vancomycin Administration for Surgical Site Prophylaxis: Plasma and Soft-Tissue Concentrations in Pediatric Neurosurgical and Orthopedic Patients. (May 2020) - Brooks Peterson, Melissa; Cohen, Mindy N.; O'Neill, Brent R.; Garg, Sumeet; Child, Jason; Henthorn, Thomas K.; Galinkin, Jeffrey G.
Abstract : BACKGROUND: Vancomycin is used for antibiotic prophylaxis in pediatric surgical patients without a complete understanding of plasma and soft-tissue pharmacokinetics. Guidelines recommend incision within 60 minutes after administration; however, tissue vancomycin concentrations at that early time may not be therapeutic. We conducted a study of plasma and skin concentrations in pediatric neurosurgical and orthopedic patients to characterize intraoperative vancomycin pharmacokinetics. METHODS: Patients (0.1–18.8 years of age) undergoing posterior spinal fusion (n = 30) or ventriculoperitoneal shunt placement (n = 30) received intravenous vancomycin 15 mg/kg (maximum 1000 mg) over 1 hour. Skin was biopsied at incision and skin closure. Blood samples were collected at incision, at 2 and 4 hours intraoperatively, and at closure. Population pharmacokinetic analysis was performed to characterize pharmacokinetic parameter estimates and to develop a model of intraoperative plasma and skin vancomycin concentrations versus time. RESULTS: Pharmacokinetic analysis included data from 59 subjects, 130 plasma samples, and 107 skin samples. A 2-compartment model, volume of the central ( V c ) and volume of the peripheral compartment ( V 2 ), proved to have the best fit. Stepwise covariate selection yielded a significant relationship for body surface area on elimination clearance and body weight on V 2 . Skin vancomycin concentrations rose continuously during surgery. Modeling predicted that equilibration of skin and plasma vancomycin concentrations took ≥5 hours. CONCLUSIONS: Skin vancomycin concentrations immediately after a preoperative dose are relatively low compared with concentrations at the end of surgery. It may be advisable to extend the time between dose and incision if higher skin concentrations are desired at the start of surgery.